Carbon Dioxide-Driven Palladium-Catalyzed C–H Activation of Amines: A Unified Approach for the Arylation of Aliphatic and Aromatic Primary and Secondary Amines - Kapoor, Mohit; Chand-Thakuri, Pratibha; Maxwell, Justin M.; Liu, Daniel; Zhou, Hanyang; Young, Michael C. (Synlett, 2019)
Amines are an important class of compounds in organic chemistry and serve as an important motif in various industries, including pharmaceuticals, agrochemicals, and biotechnology. Several methods have been developed for the C–H functionalization of amines using various directing groups, but functionalization of free amines remains a challenge. Here, we discuss our recently developed carbon dioxide driven highly site-selective γ-arylation of alkyl- and benzylic amines via a palladium-catalyzed C–H bond-activation process. By using carbon dioxide as an inexpensive, sustainable, and transient directing group, a wide variety of amines were arylated at either γ-sp3 or sp2 carbon–hydrogen bonds with high selectivity based on substrate and conditions. This newly developed strategy provides straightforward access to important scaffolds in organic and medicinal chemistry without the need for any expensive directing groups.1 Introduction2 C(sp3)–H Arylation of Aliphatic Amines3 C(sp2)–H Arylation of Benzylamines4 Mechanistic Questions5 Future Outlook
Keywords: C–H activation; carbon dioxide; amines; sustainable chemistry; organometallics; synthetic methodology